2010
DOI: 10.1111/j.1365-2486.2010.02211.x
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile salmonid populations in a temperate river system track synoptic trends in climate

Abstract: . Juvenile salmonid populations in a temperate river system track synoptic trends in climate. Global Change Biology, Wiley, 2010, 16 (12) Widespread decline among Atlantic salmon (Salmo salar) and brown trout (Salmo trutta) over recent decades have been linked to pollution, exploitation and catchment modification, but climate change is increasingly implicated. We used long-term, geographically extensive data from the Welsh River Wye, formerly a major salmon river, to examine whether climatically-mediated effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 92 publications
(145 reference statements)
3
41
0
Order By: Relevance
“…This shaded headwater provides lower water temperature in hot summers (<13°C) than the larger tributaries in the Adour basin (>15°C). Previous work on the Wye River in the United Kingdom suggested that riparian shading is crucial in maintaining Atlantic salmon in the southern part of their European range (Clews et al 2010). Although, climaterelated variables such as water temperature or rainfall can directly impact on the salmonids' preferred habitats, influencing their behavior, growth, and survival (Elliott and Elliott 2010;Swansburg et al 2002), we did not investigate those parameters nor others such as stream discharge, water chemistry, or availability of physical habitat.…”
Section: Determination Of Adult Natal Streamsmentioning
confidence: 96%
“…This shaded headwater provides lower water temperature in hot summers (<13°C) than the larger tributaries in the Adour basin (>15°C). Previous work on the Wye River in the United Kingdom suggested that riparian shading is crucial in maintaining Atlantic salmon in the southern part of their European range (Clews et al 2010). Although, climaterelated variables such as water temperature or rainfall can directly impact on the salmonids' preferred habitats, influencing their behavior, growth, and survival (Elliott and Elliott 2010;Swansburg et al 2002), we did not investigate those parameters nor others such as stream discharge, water chemistry, or availability of physical habitat.…”
Section: Determination Of Adult Natal Streamsmentioning
confidence: 96%
“…The relative importance of abiotic factors on juvenile salmonid survival and growth, such as temperature (e.g., Elliott & Elliott 1995;Jensen et al 2000;Logez & Pont 2011), flow (e.g., Cattan eo et al 2002Unfer et al 2011;Nislow & Armstrong 2012), habitat availability or a combination of these factors (Clews et al 2010), has been intensively investigated. Several studies focused on the joint effects of fish density and temperature (Crozier et al 2010;Bal et al 2011;Parra et al 2012;Baerum et al 2013) or densities and flow (Lob on-Cervi a 2004; Lobon-Cervia 2007b; Teichert et al 2010;Cunjak et al 2013), but only a few have addressed the combined effects of cohort densities (intra-and intercohort relationships) and environmental features (temperature and flow; but see Carline 2006;Grossman et al 2010Grossman et al , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Rivers are most sensitive to climate change as they are directly affected by both changes in temperature and changes in rainfall (Ormerod, ). It has been suggested that population declines seen in Atlantic salmon are a result of warmer, dryer summers (Clews et al ., ). The way in which climate change will impact freshwater species over the next decade is difficult to predict (Joint Nature Conservation Committee, ); however, some studies suggest that a rise in temperature may have already impacted Atlantic salmon (Clews et al ., ).…”
Section: Discussionmentioning
confidence: 99%